Myositis an evolving spectrum of disease. Issue 2 (3rd April 2018) - Barsotti, Simone; Lundberg, Ingrid E.
Abstract: The idiopathic inflammatory myopathies (IIMs) are a heterogeneous group of disorders characterized, as common feature, by inflammation of skeletal muscle and muscle weakness. Traditionally, IIMs have been subclassified in into polymyositis, dermatomyositis and inclusion body myositis, but this subclassification has several limitations, because clinical features as well as treatment response vary within the three IIM subgroups. In the last years several novel autoantibodies in patients with IIMs have been identified. These autoantibodies can be myositis-specific autoantibodies (MSAs) or myositis-associated autoantibodies (MAAs) and they may lead to a new approach to the classification of IIMs. This novel approach could help to subdivide patients in more homogeneous groups because, it is very rare that a patient has more than one MSAs positivity and each autoantibody is frequently associated with specific clinical features. Moreover, MSAs can help to identify subsets of IIMs also without muscular symptoms, like patients in which skin manifestations, arthritis or interstitial lung disease represent the main clinical feature. Additionally, as some autoantibodies may be associated to markedly severe manifestations, such as cancer or rapidly progressive interstitial lung disease, they can also provide a prognostic stratification of the patients.